Comparison of Direct Pars Repair Techniques of Spondylolysis in Pediatric and Adolescent Patients: Pars Compression Screw Versus Pedicle Screw-Rod-Hook. Issue 7 (August 2016) - Karatas, Ali F.; Dede, Ozgur; Atanda, Alfred A.; Holmes, Larry; Rogers, Kenneth; Gabos, Peter; Shah, Suken A.
Abstract : Study Design: Retrospective clinical cohort study. Objective: To compare the clinical and radiographic outcomes of patients who were treated with intrasegmental pars fixation by either laminar compression screw (LS) or a pedicle screw, rod, and laminar hook (PSRH) construct. Summary of Background Data: Spondylolysis is a nonunion defect of the pars interarticularis. In symptomatic spondylolysis, direct repair of the pars interarticularis defect can preserve motion and prevent abnormal stresses at the adjacent levels. Methods: Sixteen patients who failed nonoperative treatment and underwent direct pars repair by using LS (n=9) or PSRH (n=7) constructs were included in the study. Clinical outcome was assessed by using the MacNab criteria. Radiologic fusion and complications were evaluated using plain radiographs or computed tomography images and patient charts. Results: The healing rate was 100% after 6 months. The healing time was similar in both the groups: LS, 6.5 months; PSRH, 6.2 months. Patients with PSRH (5.9 mo) were more likely to return to sports earlier relative to patients with LS (7.7 mo). There were no complications in the LS group; in the PSRH group, 1 patient had mild sensory deficit and 2 had superficial wound infections. The MacNab criteria for pain assessment showed an excellent or good outcome in 8 of 9 patients in LS group and 6 of 7 patients in PSRH group. Relative to LS patients, there was a significant increase in surgical time and estimated blood loss among PSRH patients. Conclusions: Either of the mentioned 2 techniques appears to produce acceptable results. Biplanar fluoroscopy and navigation systems could minimize the risk of screw misplacement with LS construct. Familiarity with the various fixation techniques will allow the surgeon to select the most appropriate surgical technique.